2008
DOI: 10.1007/s00213-008-1280-y
|View full text |Cite
|
Sign up to set email alerts
|

The facilitative effects of d-cycloserine on extinction of a cocaine-induced conditioned place preference can be long lasting and resistant to reinstatement

Abstract: Extinction of appetitive conditioning is facilitated by DCS after 1-3 post-spaced trial injections, and retention is lasting and resistant to reinstatement. The facilitative effects appear early in extinction, but when extinction procedures are intensive, DCS appears to have no additional benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 21 publications
9
91
1
Order By: Relevance
“…The latter is unlikely because E 2 would have also interfered with reconsolidation of extinction and our design employed repeated and prolonged exposure to the context, which favors the formation of extinction memories (Mamiya et al 2009). Moreover, there is substantial evidence that E 2 treatment enhances memory consolidation in other learning paradigms (Packard and Teather 1997;Gresack and Frick 2006a), and emerging evidence that cognitive enhancers administered during the consolidation window can facilitate extinction of cocaine (Botreau et al 2006;Paolone et al 2009) or amphetamine CPP (Schroeder and Packard 2003). Although the mnemonic and neural mechanisms underlying E 2 -induced enhancement of extinction remain unknown, the present experiments are the first to demonstrate that E 2 facilitates extinction of cocaine seeking in female rats.…”
Section: Discussionmentioning
confidence: 60%
“…The latter is unlikely because E 2 would have also interfered with reconsolidation of extinction and our design employed repeated and prolonged exposure to the context, which favors the formation of extinction memories (Mamiya et al 2009). Moreover, there is substantial evidence that E 2 treatment enhances memory consolidation in other learning paradigms (Packard and Teather 1997;Gresack and Frick 2006a), and emerging evidence that cognitive enhancers administered during the consolidation window can facilitate extinction of cocaine (Botreau et al 2006;Paolone et al 2009) or amphetamine CPP (Schroeder and Packard 2003). Although the mnemonic and neural mechanisms underlying E 2 -induced enhancement of extinction remain unknown, the present experiments are the first to demonstrate that E 2 facilitates extinction of cocaine seeking in female rats.…”
Section: Discussionmentioning
confidence: 60%
“…This persistent conditioned hyperactivity in the SRÀ/À subjects supports the conclusion that intact NMDA receptor signaling is critical to extinction learning. This genetic evidence builds upon pharmacological findings with augmented GMS activation (Paolone et al, 2009;Thanos et al, 2009;Myers and Carlezon, 2010) in models of drug-associated conditioning and suggests that NMDA receptor hypofunction may be a pathophysiological feature that increases susceptibility to addiction by inhibiting the extinction of conditioned behavior. Acquisition of behavioral sensitization was also affected by altered GMS activation, with the GlyT1À/ + subjects showing a hastened rate of acquisition and the SRÀ/À subjects showing a delayed rate.…”
Section: Discussionmentioning
confidence: 76%
“…Recent research has demonstrated that inhibiting presynaptic glutamate inhibitory autoreceptors, and thus augmenting glutamatergic synaptic neurotransmission, reduced craving in cocaine-addicted patients (Amen et al, 2011). Preclinical work with the GMS partial agonist Dcycloserine demonstrates that the selective potentiation of NMDA receptor signaling may be an effective means of enhancing extinction of drug conditioning (Paolone et al, 2009;Thanos et al, 2009;Myers and Carlezon, 2010), in a manner similar to the extinction of conditioned fear in agoraphobic patients (Ressler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, most of what is known about the neural mechanisms of extinction learning was derived from studies that use aversive conditioning (e.g., footshock) or appetitive conditioning with natural rewards (e.g., food). The extinction of conditioned fear in both animals and humans [69][70][71][72][73][74][75][76][77][78][79][80] as well as a cocaine CPP [81][82][83] can be facilitated by the cognitive enhancing drug D-4-amino-3-isoxazolidone [D-cycloserine (DCS)], which is a partial agonist at the strychnine-insensitive glycine site of Nmethyl-D-aspartate (NMDA) receptors [84,85]. Nic Dhonnchadha and colleagues recently found that DCS enhances the extinction learning process and inhibits reacquisition of drug self-administration in rats trained to self-administer cocaine [86].…”
Section: The Neurobiological Substrates Of Extinction Learningmentioning
confidence: 99%